Spousal communication and socio-demographic variables as predictors of domestic violence among married couples - Uye, Emmanuel E.; Ehondor, Esohe G; Sholarin, Abiola E. (Journal of Indonesian Psychological Science (JIPS), 2023)
The menace of domestic violence has continued to shake many marriages in Nigeria with attendance consequences on the couples, children and society. Studies have examined factors predicting domestic violence with contradicting results. Therefore, this study examined spousal communication and socio-demographic predictors of domestic violence among married couples. The study adopted cross-sectional survey design while purposive sampling technique was used to select three communities in Ketu Local Government Area in Lagos State. Data were collected from 250 participants using validated questionnaires. Data collected were analysed to test two hypotheses. The result showed significant relationship between spousal communication, income level and domestic violence. Also, the result indicated that spousal communication and income level jointly predicted domestic violence. Furthermore, spousal communication, income level, number of children and length of years in marriage independently predicted domestic violence. The study concluded that spousal communication and socio-demographic variables were strong predictors of domestic violence. It is recommended that married couples should create quality time for communication among themselves KEY WORDS: domestic violence; income level; spousal communication ABSTRAK Ancaman kekerasan dalam rumah tangga terus mengguncang banyak pernikahan di Nigeria dengan konsekuensi yang terjadi pada pasangan, anak-anak, dan masyarakat. Studi telah menguji faktor-faktor yang memprediksi kekerasan dalam rumah tangga dengan hasil yang bertentangan. Oleh karena itu, penelitian ini menguji komunikasi antarsuami-istri dan prediktor sosiodemografi dari kekerasan dalam rumah tangga di antara pasangan yang sudah menikah. Studi ini mengadopsi desain survei lintas-seksional sementara teknik pemilihan sampel yang disengaja digunakan untuk memilih tiga komunitas di Wilayah Pemerintahan Lokal Ketu di Negara Bagian Lagos. Data dikumpulkan dari 250 peserta menggunakan kuesioner yang telah divalidasi. Data yang terkumpul dianalisis untuk menguji dua hipotesis. Hasil menunjukkan hubungan yang signifikan antara komunikasi antarsuami-istri, tingkat pendapatan, dan kekerasan dalam rumah tangga. Juga, hasil tersebut menunjukkan bahwa komunikasi antarsuami-istri dan tingkat pendapatan secara bersama-sama memprediksi kekerasan dalam rumah tangga. Selain itu, komunikasi antarsuami-istri, tingkat pendapatan, jumlah anak, dan lamanya tahun dalam pernikahan secara independen memprediksi kekerasan dalam rumah tangga. Studi ini menyimpulkan bahwa komunikasi antarsuami-istri dan variabel sosiodemografi merupakan prediktor kuat dari kekerasan dalam rumah tangga. Disarankan agar pasangan yang sudah menikah menciptakan waktu berkualitas untuk berkomunikasi di antara mereka sendiri.Top of FormBottom of Form KATA KUNCI KDRT; tingkat pendapatan; komunikasi antar suami-istri Copyright ©2023. The Authors. Published by Journal of Indonesian Psychological Science (JIPS). This is an open access article under the CC BY NO SA. link: Creative Commons — Attribution-NonCommercial-ShareAlike 4.0 International — CC BY-NC-SA 4.0